Juvenile Justitia and the protection of children's rights in Europe: the practice of the European Court of Human Rights - Bodnaruk, Mykola; Melenko, Serhiy; Omelchuk, Liubov; Radchenko, Liliya; Levenets, Anzhela (Cuestiones Políticas, 2021)
The objective of the research is to analyze the main violations of children's rights within the European Convention on Human Rights to highlight the basic positions of the European Court of Human Rights ECHR on their protection, as well as to determine the advisability of applying the practice of this court by the European states. The methodological basis of the work consists of different methods, such as analysis and synthesis, dialectical, logical-legal and formal-legal. The result of this work allowed identifying the role of the decisions of the European Court of Human Rights as a source of European law and its importance for the protection of the rights of the child, interpreting the legal positions established in the pertinent decisions of the said court and comparing them, to justify the need for your careful observation of the practice of the ECHR in the application of the law. It is concluded that the practice of the ECHR is recognized as a source of law in most states. And although the Ukrainian legal tradition does not recognize the status of judicial precedent as a source of law, such precedents are actively used in everyday legal activity.
Keywords: youth policy; European Court of Human Rights; European Court of Human Rights; Convention on the Rights of the Child; legal reality of Ukraine